Licensing of Regulatory Pest Control Applicators in Florida - Frederick M. Fishel (EDIS)
PI-154, a 3-page fact sheet by Frederick M. Fishel, explains the licensing and regulation of persons who apply restricted use pesticide applications to control regulated pests in Florida. Published by the UF Pesticide Information Office, June 2007.